A invenção da escola no Araguaia-Xingu mato-grossense : memórias, narrativas e lutas pela educação popular e democrática (1960-2018) - Oliveira, Edevamilton de Lima (2018)
The present work deals with The invention of the Araguaia-Xingu school in Mato Grosso: memories, narratives and struggles for popular and democratic education (1960-2018). Taking a look at the invention of the school for squatters, natives, pedestrians and their relationship with farmers, politicians, merchants and police, made it possible to understand the people's constitution, origins, life and resistance projects, choosing school as a watchtower and mechanism of power . A plot that revealed the leading leaders and, among them, the teachers who taught subversive history. The narrative also deals with framing the popular and democratic school project, 'sowing' and 'caring' as tactics for confrontation in land disputes. In this real-life plot, surrounded by specificities, were the schools sown between the Araguaia and Xingu rivers, outlining Central Brazil. However, far from the 'demographic void', many 'communities' around them, even though physically distant from the great centers, articulated with other 'communities' sharing ideas, evaluating practices and suggesting new ideas - the invention of the local school with global dimensions. The schoolchildren made (does) the Human History of the backlands of the Araguaia-Xingu Mato Grosso. Thinking about the basic education school in the second half of the twentieth century in Mato Grosso, especially during the period of military dictatorship, is important in that it revealed discourses and practices of government and the popular, revealing the latter was our purpose. In this 'bathtub' we put our boat to navigate in search of less revolting waters, however, between backwaters and rapids we came across memories, history teaching, teacher training, which projected new needs, visit the daily school of the century, dialogue with teachers and understand the social role of school in time. Revisiting his daily life gave rise to guerrilla tactics as well as the 'not told' about his invention, his popular and democratic project giving new contours to INAJÁ, and, as a result, Parceladas. Narratives and the fight for memory were the guiding thread of the history we are now sharing, gathering arguments to confront statements about the 'proclaimed bankruptcy of education' in vogue in the discourse of the oppressors. We will have to fight them in the field of knowledge, memory and history teaching, in the search for the reinvention of a popular school and democracy in times of cyberculture, of mobile devices, of the inverted classroom, of augmented reality in which one learns anywhere, anytime. Thus, we experience the expansion of relationships and transformation of the mediation of learning and knowledge transforming the reality of schoolchildren in the perspective of dialectics. Reinventing school in the expectation of a sustainable school, proper to the 21st century. Keywords: Popular education, history teaching, teacher training, digital social technologies, technology in education and sustainable school.